Do Self-Efficacy and Moral Intelligence have a Role in the Formation of Sportsmanship Behavior? - Turan, Serhat; Alemdar, Ugur; Comert, Esra; Ozcan, Hacer; Osmanoglu, Kerem (Asian Journal of Education and Training, 2022)
The present study is aimed to investigate the effect of empathy, conscience, self-control, kindness and self-efficacy on sportsmanship behaviors, since there is no study that investigated the effects of self-efficacy and moral intelligence on sportsmanship behaviors. For this purpose, the study was carried out according to the relational screening design, which is one of the quantitative research designs. 397 students studying at the faculty of sports sciences participated in the research. "Yakut-Moral Intelligence Scale", "Athlete Self Efficacy Scale" and "Investigation of Sportsmanship Behaviors Scale" were used to carry out the study. Statistical analyzes were made in SPSS 25 program and Pearson correlation and multiple linear regression analysis were used. As a result of the analysis, sportsmanship has been determined that it has a significant relationship with empathy, conscience, self-control, kindness and self-efficacy. As another result of the study, while self-efficacy alone explains 13.4% of sportsmanship, self-efficacy, empathy, self-control and kindness together explain 48% of sportsmanship. It was determined that the sub-dimension of conscience did not have a significant effect on sportsmanship. According to these results, in displaying sportsmanship behaviors; Having a high level of self-efficacy, ability to empathize, power to control behaviors and kindness have an important and powerful effect.